2012
DOI: 10.1185/03007995.2012.702101
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Parkinson’s disease pharmacotherapy from the patients’ perspective: a questionnaire-based survey

Abstract: PD has a major impact on patients' quality of life. From the patient's perspective, PD pharmacotherapy needs to address a range of symptoms including not only motor symptoms, but also non-motor symptoms such as sleep disturbances. In selecting the most appropriate treatment regimen, patient preference is an important consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…In addition to caregiver and physician assessments of PD therapy, knowledge of patients' treatment needs is also an important requirement for comprehensive long-term patient care. The findings from the current study are in line with a questionnaire-based patient survey, which indicated that patients' preferred PD therapy formulations were a once daily patch or a once daily tablet 26 . Moreover, most patients rated continuous drug delivery over 24 hours, 24 hour symptom control and nondependency on meals as important properties of a PD medication 26 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to caregiver and physician assessments of PD therapy, knowledge of patients' treatment needs is also an important requirement for comprehensive long-term patient care. The findings from the current study are in line with a questionnaire-based patient survey, which indicated that patients' preferred PD therapy formulations were a once daily patch or a once daily tablet 26 . Moreover, most patients rated continuous drug delivery over 24 hours, 24 hour symptom control and nondependency on meals as important properties of a PD medication 26 .…”
Section: Discussionsupporting
confidence: 83%
“…The findings from the current study are in line with a questionnaire-based patient survey, which indicated that patients' preferred PD therapy formulations were a once daily patch or a once daily tablet 26 . Moreover, most patients rated continuous drug delivery over 24 hours, 24 hour symptom control and nondependency on meals as important properties of a PD medication 26 . It is notable that similar results have been observed in terms of treatment preferences in studies of patients with Alzheimer's disease, a common neurodegenerative disorder which also requires a high level of caregiver support.…”
Section: Discussionsupporting
confidence: 83%
“…Among the motor complications associated with levodopa therapy and disease progression early morning akinesia, which refers to the occurrence of clinically significant parkinsonism preceding the administration of the first daily dose of dopamine replacement agents, has been recently identified as a significant source of discomfort by 55.4% of 6351 respondents of an anonymous survey carried out among German PD patients [90]. A supplemental dose of levodopa taken upon awakening has been proven to be beneficial in this circumstance, with its effect shown to reach clinical significance within 15-75 minutes after drug ingestion [91].…”
Section: Wearing-offmentioning
confidence: 99%
“…Disease‐specific QoL questionnaires can, however, be relatively tautological, providing results that are difficult to interpret because of lack of external reference . Furthermore, from the patient's perspective, PD pharmacotherapy needs to address a range of symptoms, including non‐motor symptoms in addition to motor symptoms . Lastly, it is important to note that the generic HRQoL instruments in the present study were sufficiently sensitive to show some decline in HRQoL, even within the short interval of 6 months.…”
Section: Discussionmentioning
confidence: 85%